Percutaneous Transforaminal Full-Endoscopic Removal of Neurinoma of the Fifth Lumbar Nerve Root With Intraoperative Neuromonitoring: A Case Report - Kravtsov, Maxim N.; Manukovsky, Vadim A.; Mirzametov, Saidmirze D.; Malysheva, Olga V.; Averyanov, Dmitry A.; Svistov, Dmitry V. (Frontiers in Surgery, 2022)
Background: Technical achievements and surgical techniques improvement contribute to the expansion of the endoscopic spine surgery possibilities. However, today there are few reports about the use of percutaneous percutaneous endoscopy in spinal tumors surgery. A case of percutaneous transforaminal endoscopic removal of the lumbar spinal nerve tumor with intraoperative neuromonitoring is presented. Case description: A 59-year-old female was complaining of a left shin and foot pain, weakness and paresthesia. Preoperative magnetic resonance imaging revealed a tumor (neurinoma) at the left L5-S1 intervertebral foramen. Transforaminal endoscopic removal of an extramedullary tumor from an 8 mm skin incision with intraoperative neuromonitoring was performed. Postoperative MRI revealed signs of total resection of the tumor. Conclusion: The presented case confirms that percutaneous endoscopic removal of lumbar spine intraforaminal neurinomas can be safe and effective.